Effect of inferior alveolar nerve transection on the inorganic component of bone of rat mandible - Němec, Ivo; Smrčka, Václav; Mihaljevič, Martin; Hill, Martin; Pokorný, Jaroslav (Journal of musculoskeletal & neuronal interactions, 2020)
OBJECTIVE: The aim of the study was to test the effect of transecting the inferior alveolar nerve on the inorganic bone component of the rat mandible. METHODS: 7-9 weeks old, male Wistar rats were used for the study. The animals were divided in 3 groups: control, experimental (nerve was transected) and sham (nerve was only prepared but not transected). After 4 weeks, the animals were killed, their teeth were extracted, and the mandibular bone was divided in 4 parts. Inductively coupled plasma mass spectrometry was used to the levels of 7 elements in the bone. RESULTS: The study results demonstrate that transection of the inferior alveolar nerve caused a decrease in calcium, iron, and strontium, and an increase of zinc. It caused the differences in potassium contents between the sides was significantly lower in the experimental group. The increase in the magnesium content, and decrease of sodium and potassium in the experimental group, as well as differences in the contents of: magnesium, sodium, potassium, iron and zinc between individual locations in the mandible are associated with the surgical approach. CONCLUSION: The results support our hypothesis - that sensory innervation has an impact on the inorganic component of the mandibular bone.
Keywords: Nerve Transection; Inferior Alveolar Nerve; nervus mandibularis; krysa rodu Rattus; Elements; Axotomy; Male; Mandible; Animals; Rats, Wistar; mužské pohlaví; potkani Wistar; Mandibular Nerve; mandibula; zvířata; axotomie; Rats